INVESTIGATING THE PSYCHOMETRIC PROPERTIES OF THE PICTORIAL FIT-FRAIL SCALE. (11th November 2018) - McGarrigle, L; Squires, E; Wallace, L; Gorman, M; Rockwood, K; Theou, O
Abstract: The recently developed Pictorial Fit-Frail Scale (PFFS) is an image-based tool that was designed to be easy to administer, sensitive to cultural differences, and a practical approach to identifying frailty compared to other frailty measures. The feasibility, reliability, validity, and responsiveness of the PFFS are currently being tested across three settings: geriatric day hospital (GDH), memory clinic, and primary care clinic. Preliminary analysis was conducted on data from all sites (n=80) to investigate the feasibility (time taken to complete the scale) and inter-rater reliability of the PFFS. Test-rest reliability was conducted on GDH data where patients attended at two time-points (retest within 7–14 days of initial visit; n=42). At all sites, when available, caregivers, nurses, and physicians completed the scale based on the patients' health. PFFS scores can range from 0–43. A Frailty Index (FI) was constructed based on PFFS scores. Time taken to complete the scale was 4.9 ± 2.4 minutes for patients (n=46), 3.5 ± 1.4 for caregivers (n=43), 1.5 ± 1.1 for nurses (n=72), and 1.9 ± 2.0 for physicians (n=42). Mean patient PFFS score was 15.2 ± 7.0 (FI=0.36 ± 0.16), mean caregiver score was 19.9 ± 8.6 (FI=0.46 ± 0.20), mean nurse score was 15.4 ± 7.5 (FI=0.36 ± 0.18), and mean physician score was 19.2 ± 8.0 (FI=0.44 ± 0.18). There was no significant difference in scores between raters (p>.05). Test-retest reliability was good for patients (ICC=0.70) and nurses (ICC=0.80). Inter-rater reliability between patients/caregivers (ICC=0.83) and nurses/physicians (ICC=0.87) was good. Preliminary findings suggest the PFFS is a feasible and reliable tool, however further analysis is necessary with a larger sample.